A New Approach: Closing the Writing Gap By Using Reliable Assessment to Guide and Evaluate Cross-Curricular Argumentative Writing - (:unkn) unknown (My University, 2016)
Educational standards emphasize cross-curricular literacy and complex skills at the secondary level. These standards align to the heightened priority of argumentative writing across disciplines. With increasingly complex and shifting writing expectations, assessment practices need to be implemented to mirror these expectations. Two primary components to effective assessment are the ability to inform teaching and improve student learning. This study is designed to test the reliability of a process-oriented rubric as a tool to evaluate argumentative writing in the cross-curricular context, and as a tool to guide classroom practices based on student readiness. The purpose of this study is to observe the reliability of a process-oriented argumentative writing rubric as an evaluation tool, and to measure the reliability of a process-oriented argumentative writing rubric that informs instruction. Teachers and their students from two inclusive, urban education classes participated in the study. One class represented a control group which received the first and last treatment conditions without experimental interventions. The second class represented an experimental group that engaged in a tiered intervention program guided by the assessment tool. Additionally, four reported educators participated in analyzing the tool’s reliability as a cross-curricular rubric for argumentative writing. The educators also completed surveys about their experiences using the rubric created for the study and traditional assessment practices. Results suggest that tiered intervention guided by effective assessment makes significant gains in literacy achievement over a short period of time. Results also suggest that the rubric created for the study warranted more reliable ratings across cross-curricular educators than traditional assessment. Educators also reported a preference for the process-oriented approach to assessment over traditional methods.
Keywords: Argumentative Writing; Assessment; Complexity; Literacy; Process-Oriented; Reliability